Oblicza melancholii. Szafa Olgi Tokarczuk i jej chorwacki przekład - Majdzik, Katarzyna (Przekłady Literatur Słowiańskich, 2012)
The Faces of Melancholy The Wardrobe by Olga Tokarczuk and its translation into Croatian The aim of this article is to illustrate the phenomenon of melancholy, its sources, mechanisms and modes of existence. Basing on The Wardrobe by Olga Tokarczuk and its Croatian translation the author tries to demonstrate a relation between melancholy and language, she considers the art as a kind of fight against nothingness (and melancholy) and explores the textual manifestation of melancholic subjectivity. A psychoanalytic approach to melancholy aids to determine the condition of text (the translated text in particular). The image of melancholy reconstructed from The Wardrobe is a culture-independent phenomenon. The universalism of melancholy and the allegorical nature of Tokarczuk’s work remove barriers between original and translated text culture facilitating the act of translation. The main source of cultural barriers, in this case, are the linguistic (mainly grammatical) differences. Key words: melancholy, subjectivity, psychoanalysis, translation, interpretation.